Notes on the lightlike hypersurfaces along spacelike submanifolds - Ekmekci, F. N.; Tuğ, G. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 514.7 In the light of the method of construction of lightlike hypersurfaces along spacelike submanifolds, we give a relation between the second fundamental form of a spacelike submanifold and the screen second fundamental form of the corresponding lightlike hypersurface. In addition, we investigate the conditions for a lightlike hypersurface of this kind to be screen conformal.